Relationship between cortisone and muscle work in determining muscle size - Goldberg, A. L. (1969)
1. Large doses of cortisone caused marked atrophy of the plantaris muscle and other pale muscles of hind limbs of hypophysectomized rats, but hormone treatment had little effect on the size of the red soleus muscle. 2. Denervation increased the sensitivity of the soleus and plantaris to the catabolic effects of cortisone. 3. Increased work induced by tenotomy of the synergistic gastrocnemius made the plantaris muscle less sensitive to cortisone-induced atrophy. 4. Since the catabolic effects of cortisone are more pronounced in the less active muscles, it is suggested that in mobilizing body protein for gluconeogenesis the hormone spares those muscles physiologically most active. 5. The rapidity with which muscles lose weight in response to cortisone indicates that the hormone must decrease protein half-lives as well as decrease protein synthesis.